(untitled) (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2025)
about who met the last days of the life of Maqsud Shaykhzoda, a conversation with people with whom he met. The mistress was going out into the kitchen and singing with the intention of swimming a liquid dish, my mistress walked in. - Honey, don’t be too obsessed. We will not die long. Domlangiz is not in good condition. "Come out, don’t bother too much,” domlangiz says.